UNDERPRICING, LONG-TERM PERFORMANCE, AND POLITICAL CONNECTION OF INDONESIAN IPOS - Eka Saputra, Albert
Initial Public Offering (IPO) is an activity of the company in order to offer their shares in public. After the IPO, one of the main concerns for both the firms and investors are the performance of the stock, both in short- and long-term. It is expected that the firm price will increase, giving higher value to the firms and better return for investors. However, firms with different characteristics may perform differently. Therefore, this study aims to investigates (1) short-run (IPO-day return) and long-run (one-to-five-year return) performance of IPOs listed in Indonesia Stock Exchange (IHSG), (2) politically connected IPO firms (POLCON) and its post-IPO performance, and (3) factors influencing that performances. Through this paper, a total of 168 IPOs listed and traded for a period year of 2005 to 2013 are deeply examined. It is believed that non-financial factors, namely political connection significantly affect the rate of return of the stock. Aligned with what previous studies found, in short-run, our findings show that IPO firms are underpriced by 23.18%, while POLCON experiences 23.45%, with no mean difference found. In long-run, IPO firms are found to underperform the market significantly, examined by buy-and-hold abnormal return (BHAR) in equalweighted and value-weighted method. Furthermore, POLCON experience better performance compared to those without political connection based on five-year post-IPO stock return. Firms with higher underpricing rate are also found to have poorer long-term performance. Finally, this study provides new and comprehensive guideline to investors that it is more profitable to invest in politically unconnected firms for short-term and invest in politically connected firms in long-term.